An Experimental Investigation of Free Space Cooling by Phase Change Material (PCM) - Kulkarni, R. R.; Shaikh, Ummid; Chavan, Priyanka (Penerbit Universiti Malaysia Pahang, 2015)

(untitled)
In free space cooling PCM at suitable melting point is solidified by using night time cold air. During day time room air is passed over the solid PCM which absorbs Latent heat from it and melts. As a result room air gets cooled. In the present work suitable double pipe heat exchanger is designed and manufactured for the experimentation. The inner pipe is made up of copper and outer pipe with acrylic for visualization of phase change. PCM LatestTM29T (hydrated salt)is filled in annular space and atmospheric air is passed through inner tube. Air flow velocity is measured by hot-wire anemometer. 8 RTD sensors are placed at different location, 2 for inlet and outlet temperature and 6 are inserted in the PCM at different radial locations.The real time temperature data is captured by 8 channel Data Acquisition System at an interval of 15 minutes. A 90 W Centrifugal blower with VFD controller is used for passing the air with different velocities. The experimentation consists of passing cold outside air in the copper pipe during late night hours until PCM solidifies and measurement of solidification time. During day time hot room air is passed through tube and melting time and temperature dropof air is measured.It is observed thatabout 90% of PCM solidifies in about 7 hours when the night time ambient temperature is 220C with airvelocity of 12 m/s. During day time melting hoursof PCM are found to be 6.5 hours with inlet average temperature of air to be 340C, with 4m/s velocity and average temperature drop of 0.8 0C is observed.